Revealing The Exotic Rhythm and Tonality in Bright Sheng’s Dance Capriccio - Deng, Qian; Chiat, Loo Fung (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2023)
For the different embodiments of exotic styles in musical compositions, composers have provided a number of examples of patterns and new directions, broadly summarizing it as the musical characteristics of a different region, whether apparent or not, that are reflected in a musical work. Bright Sheng is one of the leading Chinese-American whose significant works exhibits a strong exotic style using Western compositional technique. This article analyses Sheng’s Dance Capriccio composed in 2011, featuring Sherpa folk music. The analysis focuses on how Sherpa folk song and dance are reflected in Dance Capriccio, emphasizing how the tonal and rhythmic construction reflects the traditional folk song. It is also gathered that the gestural movement of Sherpa dances are reflected in this work. This paper will provide an insight into the infinite possibilities of modernist works through the integration and narration with exotic characteristics.